REKONTRUKSI MODEL OPERASIONAL ASURANSI UMUM SYARIAH; STUDI KUALITATIF ATAS IMPLEMENTASI AKAD TABARRU’ - Yurahman, LindaMarlinda; Sobarna, Nanang (EKSYDA: Jurnal Studi Ekonomi Syariah, 2025)
The inconsistency between the principle of tabarru' contracts and the operational practices of general sharia insurance in Indonesia remains a crucial issue in the development of the takaful industry. Problems such as the mixing of contract types, the absence of fund separation between participants and operators, and the lack of implementation of maqasid sharia values, create legal uncertainty and reduce the effectiveness of institutions. This study aims to reconstruct the operational system of general sharia insurance with a conceptual approach that prioritises tabarru' contracts and the integration of Maqasid Sharia. The approach used is descriptive qualitative through literature study, referring to the fatwas of DSN-MUI, OJK regulations, fiqh muamalah literature, and scientific articles. The results of the study formulate five main elements of an ideal operational system: clarity of contract structure, a fair contribution system, transparent management of risk and surplus funds, separation of participant and operator funds, and the application of maqasid sharia principles. Overall in the governance of institutions. This finding underscores the importance of formulating a standard operational model that not only complies formally but also substantially reflects the objectives of Sharia. The main contribution of this research is to provide a theoretical foundation and practical input for the development of national operational policies for the Sharia insurance industry.